2021
DOI: 10.1088/1741-4326/abf0dd
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic simulation of low-frequency Alfvénic modes in DIII-D tokamak

Abstract: Global gyrokinetic simulations find that a beta-induced Alfvén eigenmode (BAE) and a low-frequency mode (LFM) co-exist in the DIII-D tokamak experiments. The simulated LFM mode structure and many of its parametric dependencies are consistent with experimental observations. The LFM can be excited without fast ions and has a frequency inside the gap of the beta-induced Alfvén-acoustic eigenmode (BAAE). However, an antenna scan shows that it is NOT the conventional BAAE. Instead, the LFM is an interchange-like el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…Furthermore, GTC has also incorporated compressible magnetic perturbations to maintain perpendicular force balance [29], which have been neglected in most of the previous gyrokinetic simulations. Recent GTC simulations found that these compressible magnetic perturbations can be important for interchange-like modes [29,30] with realistic β (ratio of kinetic pressure to magnetic pressure) in tokamak plasmas, consistent with analytic theory [31,32].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, GTC has also incorporated compressible magnetic perturbations to maintain perpendicular force balance [29], which have been neglected in most of the previous gyrokinetic simulations. Recent GTC simulations found that these compressible magnetic perturbations can be important for interchange-like modes [29,30] with realistic β (ratio of kinetic pressure to magnetic pressure) in tokamak plasmas, consistent with analytic theory [31,32].…”
Section: Introductionsupporting
confidence: 60%
“…Note that this model incorporates the compressible magnetic perturbation δB to maintain perpendicular force balance. The effects of the compressible magnetic perturbation δB , which have been neglected in most of gyrokinetic simulations, can be very important even for modest beta when simulating low frequency MHD modes such as interchange and kink instabilities for realistic β in existing and future tokamak plasmas [30][31][32]44]. The same argument also holds for a broad class of long wavelength drift-Alfvén waves [55,56].…”
Section: Verification Of Internal Kink Simulations In Ideal Mhd Limitmentioning
confidence: 93%
“…These include the linear gyrokinetic code LIGKA [63], the ideal MHD code NOVA [64], the gyrokinetic code GTC, and the gyrofluid code FAR3d [65]. The GTC simulations are discussed in detail in [66].…”
Section: Initial Comparisons With Theorymentioning
confidence: 99%
“…The effects of the compressible magnetic perturbation δB , which has been neglected in most of gyrokinetic simulations, can be very important even for modest beta when simulating low frequency MHD modes such as interchange and kink instabilities for realistic β in existing and future tokamak plasmas [31][32][44] [30].…”
Section: Codementioning
confidence: 99%